Geographische Aspekte des Algenbaus in Japan - Aymans, Gerhard (ERDKUNDE, 1980)
Seaweeds had been gathered in Japan in their natural habitat, the coastal rocks washed by the half tide, for at least one thousand years, before some recourseful people, in 1682, succeeded in expanding the natural habitat of the winter growing red algae (Porphyra species) by setting up branches as a base for the algae spores to settle on in the waters off the coast. A further step ahead in what was to become the cultivation of seaweeds took place in 1938, when it was discovered that certain coastal waters lent themselves more to the collection of algae spores, while others were more suitable for the actual cultivation of the seaweeds growing up from the spores collected. This discovery let to a functional separation of the coastal waters into spore waters and cultivation waters. Economically, the result was a considerable increase in seaweed production. The autumnal appearance of the algae spores, however, remained subject to regional fluctuations which were technically overcome in about 1948, when the cumbersome branches as a base for the spores to settle on were substituted by lattice work and nets. In this way, transportation costs for algae spores were very much reduced, and spore collectors were enabled to send their product to any coast in which it was in demand. The most important development in seaweed production, the rearing of algae spores in fully controllable basins, began only after 1960. It goes back to the discovery of the natural life cycle of Porphyra umbicialis by the British phycologist K. M. Drew (1949). She studied and described the life cycle of the seaweed mentioned in its hitherto unknown summer phase and thus layed the foundation-stone to present day seaweed cultivation techniques in Japan. The summer phase of the life cycle of the Porphyra species cultivated in Japan to-day takes place in large basins which are fully controllable as far as the production of algae spores is concerned. Algae spores, of whatever Porphyra species, can now be produced in Japan to serve even a world market. The location of seaweed cultivation in Japan itself, however, is undergoing great changes, since the large cities are growing into the waters hitherto occupied by seaweed production.